Effect of Pd Precursor Salts on the Chemical State, Particle Size, and Performance of Activated Carbon-Supported Pd Catalysts for the Selective Hydrogenation of Palm Biodiesel - Parncheewa Udomsap; Apiluck Eiad‐ua; Shih-Yuan Chen; Takehisa Mochizuki; Nuwong Chollacoop; Yuji Yoshimura; Masayasu Nishi; Hiroyuki Tateno; Hideyuki Takagi (International Journal of Molecular Sciences, 2021)
OH. The small Pd particles gave increased selectivity toward unwanted-FAME components, particularly the saturated fatty acid methyl esters during the hydrogenation of poly-FAME. This selectivity is unprofitable for improving the biodiesel quality.
Keywords: Biodiesel Production and Applications; Catalysis and Hydrodesulfurization Studies; Catalytic Processes in Materials Science